FROM ACCOUNTING PROFESSIONAL TO TEACHING CAREER: A STUDY ON THE MOTIVATIONAL FACTORS FOR THE TRANSITION - Fernandes, Carla Milena Gonçalves; Gomes, Débora Gomes de; Souza, Marcos Antônio de (Revista Universo Contábil, 2020)
The aim of the study is to know the predominant motivational factors in the dismissal of an accounting profession and the insertion in the teaching career of professors of the Accounting Sciences Course of Brazilian Public Federal Universities. This was a descriptive and quantitative research, with the participation of 37 teachers. The two sets of assertions (professional termination and insertion in the teaching career) were correlational to verify the adjustment of the data for later application of the factorial analysis, in order to answer the study’s objective. It can be noticed that the motivations present in the first set (professional termination) belong to the introjected and identified regulations, besides the appearance of demotivation as one of the factors. Such demotivation reflects the discontent with the development of the professional career. In the second set (insertion in the teaching career), introjected, external and intrinsic motivations were found to be related to public employment stability, remuneration, relevance, pleasure and social recognition of the activity. The results obtained were considered satisfactory since they provide a visualization of the stimuli before and after the insertion in the teaching career as well as the motivating factors for the permanence in this career.